THE ROLE OF THE TRAFFIC POLICE REGARDING ROAD USERS WHO OBTAIN PRIMARY RIGHTS UNDER ARTICLE 134 OF LAW NUMBER 22 OF 2009 IN KUNINGAN DISTRICT - Lani Prasetiyani; Triwahyuningsih Triwahyuningsih (Jurnal Meta-Yuridis, 2023)
This study aims to determine the role of the Traffic Police regarding road users who have primary rights in Kuningan District. This type of qualitative research with a juridical-empirical approach. The subject of this study is the Head of Traffic Operations Development Affairs at the Kuningan Police, while the object of this research is the role of the Traffic Police regarding road users who obtain primary rights in Kuningan District. Data collection methods are interviews and documentation. The validity of the data used is triangulation technique. Data analysis techniques namely data reduction, data presentation, and conclusion. The results of this study indicate that the role of the Traffic Police regarding road users who have primary rights in Kuningan Regency, whether firefighters, ambulances, first aid vehicles, cavalcades, and convoys and/or vehicles for certain purposes, are Preventive and Repressive. Preventive is a prevention effort before violations occur in the form of escorts, patrols, and outreach through Dikmaslantas. Repressive measures are taken when prevention cannot be overcome in the form of giving warnings, fines